Counting‐loss correction for X‐ray spectroscopy using unit impulse pulse shaping. (19th February 2018) - Hong, Xu; Zhou, Jianbin; Ni, Shijun; Ma, Yingjie; Yao, Jianfeng; Zhou, Wei; Liu, Yi; Wang, Min
Abstract : A new kind of unit impulse pulse‐shaping method is proposed based on recursive calculation of a reset‐type preamplifier and a C‐R shaper. The unit impulse pulses generated in the detector are obtained in order to correct the counting loss in X‐ray spectroscopy. Abstract : High‐precision measurement of X‐ray spectra is affected by the statistical fluctuation of the X‐ray beam under low‐counting‐rate conditions. It is also limited by counting loss resulting from the dead‐time of the system and pile‐up pulse effects, especially in a high‐counting‐rate environment. In this paper a detection system based on a FAST‐SDD detector and a new kind of unit impulse pulse‐shaping method is presented, for counting‐loss correction in X‐ray spectroscopy. The unit impulse pulse‐shaping method is evolved by inverse deviation of the pulse from a reset‐type preamplifier and a C‐R shaper. It is applied to obtain the true incoming rate of the system based on a general fast–slow channel processing model. The pulses in the fast channel are shaped to unit impulse pulse shape which possesses small width and no undershoot. The counting rate in the fast channel is corrected by evaluating the dead‐time of the fast channel before it is used to correct the counting loss in the slow channel.